Implementasi Zakat Perdagangan di Desa Karangrandu Kecamatan Pecangaan Kabupaten Jepara - Lutfiah Mahmudah; Edi Susilo (Jurnal Rekoginisi Ekonomi Islam, 2023)
This study aims to determine the collection and distribution of trade zakat in Karangrandu Village, Peacanganan District, Jepara Regency needs to be carried out to increase knowledge about the Implementation of trade zakat as a reference for the community in paying, distributing and paying trade zakat. The purpose of the research based on the formulation of the problem is to find out how the implementation of trade zakat in Karangrandu Village, Pecangaan District, Jepara Regency. The method used in this research is to use qualitative research methods. The objects used by researchers are Zakat Collection Unit / Unit Pengumpulan Zakat (UPZ) administrators and traders in Karangrandu Village. These results indicate that so far it has been impressed that the distribution of zakat has not been managed professionally so that the value of zakat contained in zakat becomes invisible. Inaccuracies in the distribution of zakat and the identification of the needs of mustahik make zakat not have a broad impact but tend to make the poor as eternal mustahik. The need for traders to know and understand the awareness of zakat through the Karangrandu Village UPZ for the problem of distributing and empowering trade zakat funds that are carried out. There is still a lack of public knowledge, especially traders in zakat.